Effect of moisture stress on growth of oil palm (Elaeis guineensis) seedlings - Chin, H. F.; Sekaran Nair, K. C. (1980)
'Collante', a disorder in oil palm seedlings has been attributed to moisture deficiency; results obtained in this experiment confirmed it. One-month-old seedlings in poly bags receiving 500 cc of water at intervals of more than three days produced symptoms of collante. One-week-old seedlings failed to survive the same watering intervals. The effect of moisture stress produced symptoms of collante and the total dry matter of shoots and roots was significantly reduced.